Arabidopsis Target of Rapamycin Coordinates With Transcriptional and Epigenetic Machinery to Regulate Thermotolerance - Sharma, Mohan; Jamsheer K., Muhammed; Shukla, Brihaspati Narayan; Sharma, Manvi; Awasthi, Prakhar; Mahtha, Sanjeet Kumar; Yadav, Gitanjali; Laxmi, Ashverya (Frontiers in Plant Science, 2021)
Global warming exhibits profound effects on plant fitness and productivity. To withstand stress, plants sacrifice their growth and activate protective stress responses for ensuring survival. However, the switch between growth and stress is largely elusive. In the past decade, the role of Target of Rapamycin (TOR) linking energy and stress signalling is emerging. Here, we have identified an important role of Glucose (Glc)-TOR signalling in plant adaptation to heat stress (HS). Glc via TOR governs the transcriptome reprogramming of large number of genes involved in heat stress protection. Downstream to Glc-TOR, E2Fa signalling module regulates the transcription of heat shock factors through direct recruitment of E2Fa onto their promoter regions. Also, Glc epigenetically regulates the transcription of core HS signalling genes in a TOR-dependent manner. TOR acts in concert with p300/CREB HISTONE ACETYLTRANSFERASE1 (HAC1) and dictates the epigenetic landscape of HS loci to regulate thermotolerance. Arabidopsis plants defective in TOR and HAC1 exhibited reduced thermotolerance with a decrease in expression of core HS signalling genes. Together, our findings reveal a mechanistic framework in which Glc-TOR signalling through different modules integrates stress and energy signalling to regulate thermotolerance.